Mitochondrial sequence reveals high levels of gene flow between breeds of domestic sheep from Asia and Europe - Meadows, J. R. S.; Li, K.; Kantanen, J.; Tapio, M.; Sipos, W.; Pardeshi, V.; Gupta, V.; Calvo, J. H.; Whan, V.; Norris, B.; Kijas, J. W. (Journal of Heredity, 2005)
Sequence variation present within the mitochondrial genome was used to investigate genetic diversity within sheep breeds from Asia and Europe. Comparison of 2027 bp of sequence from 121 animals revealed 44 phylogenetically informative nucleotide positions and a single insertion/deletion. A total of 57 haplotypes were observed which formed two distinct clades. Type A haplotypes were found in breeds from Asia (India, Indonesia, Mongolia, and Tibet), while type B haplotypes were observed at the highest frequency in breeds sourced from Europe (nine breeds from Austria, angstrom land, Finland, Spain, and northwestern Russia). The distribution of haplotypes indicates sheep appear to have the weakest population structure and the highest rate of intercontinental dispersal of any domestic animal reported to date. Only 2.7% of the sequence variation observed was partitioned between continents, which is lower than both goat (approximately 10%) and cattle (approximately 50%). Diagnostic restriction fragment length polymorphism polymerase chain reaction (RFLP-PCR) tests which distinguish type A and B haplotypes were used to test an additional 223 animals from 17 breeds of European and Asian origin. A mixture of the two lineages was found in every breed except Suffolk and the Indian Garole, indicating introgression has played a major part during breed development and subsequent selection.

Mitochondrial haplotypes reveal a strong genetic structure for three Indian sheep breeds - Pardeshi, V. C.; Kadoo, Narendra Y.; Sainani, Mohini N.; Meadows, J. R. S.; Kijas, J. W.; Gupta, Vidya S. (Animal Genetics, 2007)
This survey represents the first characterization of mitochondrial DNA diversity within three breeds of Indian sheep (two strains of the Deccani breed, as well as the Bannur and Garole breeds) from different geographic regions and with divergent phenotypic characteristics. A 1061-bp fragment of the mitochondrial genome spanning the control region, a portion of the 12S rRNA gene and the complete phenyl tRNA gene, was sequenced from 73 animals and compared with the corresponding published sequence from European and Asian breeds and the European Mouflon (Ovis musimon). Analysis of all 156 sequences revealed 73 haplotypes, 52 of which belonged to the Indian breeds. The three Indian breeds had no haplotypes in common, but one Indian haplotype was shared with European and other Asian breeds. The highest nucleotide and haplotype diversity was observed in the Bannur breed (0.00355 and 0.981 respectively), while the minimum was in the Sangamneri strain of the Deccani breed (0.00167 and 0.882 respectively). All 52 Indian haplotypes belonged to mitochondrial lineage A. Therefore, these Indian sheep are distinct from other Asian and European breeds studied so far. The relationships among the haplotypes showed strong breed structure and almost no introgression among these Indian breeds, consistent with Indian sheep husbandry, which discourages genetic exchange between breeds. These results have implications for the conservation of India's ovine biodiversity and suggest a common origin for the breeds investigated.
Keywords: Genetic diversity; Indian sheep; mitochondrial DNA; mitochondrial lineage; phylogeographic distribution; sheep domestication